Raised nap artificial leather and its manufacturing method
By adding carbon black and colored pigments to extremely fine fibers, controlling the content and coloring state of polymer elastomers, combining the fiber-bearing process and polishing treatment of island-type composite fibers to form a matte surface, the problems of low friction resistance and dual-color feeling after dyeing of matte artificial leather are solved, and efficient and economical preparation of matte artificial leather is achieved.
Patent Information
- Application Number
- CN202080090272.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-25
- Filing Date
- 2020-12-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-12-03
AI Technical Summary
The existing vertical hair artificial leather has low friction resistance and low dye fastness after dyeing, and the dye fastness of polymer elastomers is lower, resulting in uneven color and two-color feeling, making it difficult to achieve advanced coloring.
By adding 0.2 to 8 mass% of carbon black and 0.1 to 5 mass% of color pigment to the extremely fine fibers, the content ratio of polymer elastomer is 0.1 to 15 mass% of polymer elastomer is not colored, and the extremely fine fibers are not dyed. The fiber-bearing process of island-type composite fibers is used to avoid using organic solvents, and the erect surface is formed directly by grinding.
It has achieved vertical hair artificial leather with excellent friction-resistant color fastness, which can achieve non-white color color in a wide range of tones from light to dark colors, and is not prone to two-color feeling, maintaining a high-end appearance and productivity.
Smart Images

Figure GDA0003711905870000141
Abstract
Description
Technical Field
[0001] The present invention relates to a napped artificial leather having a napped surface like suede leather, which can be preferably used as a surface material of clothing, shoes, furniture, car seats, sundry products, etc. More specifically, it relates to a napped artificial leather which can be colored in a wide range of colors from light to dark while maintaining high color fastness. Background Art
[0002] The napped artificial leather having a suede-like appearance has a napped surface formed by napping ultrafine fibers, the napped surface being formed by napping the surface of an artificial leather fabric produced by impregnating a polymer elastic body into gaps in a fiber entanglement body formed by entanglement of ultrafine fibers.
[0003] Dyeing is widely used to color the napped artificial leather. When dyeing is used, the napped artificial leather can be colored in a wide range of colors from light to dark. However, the dyed napped artificial leather has a problem of low color fastness such as color fastness to friction. In addition, in the dyed napped artificial leather, the color fastness of the polymer elastomer is lower than that of the ultrafine fibers. Therefore, the exposed part of the polymer elastomer in the napped surface becomes whitish, and the color unevenness caused by the different colors of the ultrafine fibers and the polymer elastomer is obvious, showing a two-color feeling, and there is a problem that it is difficult to obtain a napped artificial leather with a high-grade feel.
[0004] A method for producing a napped artificial leather having excellent color fastness, suppressed two-color feeling, and color-adjusted to a wide range of tones from bright colors to achromatic colors and from light colors to dark colors has also been proposed. For example, the following Patent Document 1 discloses that a wide range of tones are adjusted by coloring both fibers and a polymer elastic body with a pigment so that the color of the fibers and the color of the polymer elastic body are mixed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-143654 Summary of the invention
[0008] Problems to be solved by the invention
[0009] When the polymer elastomer is colored with a pigment in order to color the napped artificial leather, there is a problem that part of the pigment falls off during the solidification process of the polymer elastomer, resulting in color deviation of the product, or the switching loss of the raw material increases when the color is changed to another color during the production process. On the other hand, when the polymer elastomer is not colored, as described above, the part of the polymer elastomer exposed in the napped surface becomes white, and there is a problem that the color unevenness caused by the difference in color between the ultrafine fibers and the polymer elastomer is obvious, and a two-color feeling is presented.
[0010] The present invention aims to provide a napped artificial leather which has excellent color fastness to rubbing, can be colored in a wide range of tones from light to dark, and is not prone to two-color appearance on the napped surface even if the polymer elastomer is not colored.
[0011] Solutions to the problem
[0012] One aspect of the present invention relates to a napped artificial leather, comprising: a fiber entanglement body formed by entanglement of ultrafine fibers, and a polymer elastic body impregnated into the fiber entanglement body, wherein the napped artificial leather has a napped surface formed by napping the ultrafine fibers on at least one side, wherein the ultrafine fibers contain 0.2 to 8% by mass of carbon black and 0.1 to 5% by mass of color pigments, and the total ratio of carbon black to color pigments is 0.3 to 10% by mass, the content ratio of the polymer elastic body is 0.1 to 15% by mass, the polymer elastic body is not colored, and the ultrafine fibers are not dyed. Such a napped artificial leather is not dyed, so it has excellent color fastness to friction. In addition, since the polymer elastic body is not colored, the problem of contamination of the process that occurs when the polymer elastic body is colored with a pigment does not occur. In addition, by setting the content ratio of the polymer elastic body to 0.1 to 15% by mass, the polymer elastic body is not easily exposed on the napped surface, so that color unevenness is not easily conspicuous and a two-color feeling is not easily expressed. In addition, by coloring the ultrafine fibers with 0.2 to 8% by mass of carbon black and 0.1 to 5% by mass of color pigments, coloring with non-white tones can be achieved in a wide range of tones, and it is difficult to show a two-color feeling on the napped surface. In addition, by making the total ratio of carbon black and color pigments 0.3 to 10% by mass, it is possible to achieve both colorability and melt spinnability during production.
[0013] In addition, since it is difficult to sufficiently express a two-color effect, the mass ratio of color pigment / carbon black is preferably 0.1 to 2.0.
[0014] In addition, from the perspective of making the color unevenness less noticeable and maintaining high color fastness to rubbing even for dark colors, it is preferred that the napped surface be located in the color coordinate space (L * a * b* The brightness L in the color space) * The value is below 25, a * The value is in the range of -2.5 to 2.5, b * The value ranges from -2.5 to 2.5.
[0015] In addition, in the production of the above-mentioned napped artificial leather, there is sometimes a process using an organic solvent, such as removing one component of the sea-island type composite fiber with an organic solvent, or wet coagulating the polymer elastic body with a coagulation liquid containing an organic solvent. In the production of such napped artificial leather, there is a problem that the organic pigment added to the island component dissolves and elutes in the process using an organic solvent.
[0016] Another aspect of the present invention relates to a method for manufacturing the above-mentioned napped artificial leather, which method at least includes: a step of preparing a fiber assembly of sea-island type composite fibers having a non-water-soluble thermoplastic resin containing 0.2 to 8% by mass of carbon black and 0.1 to 5% by mass of color pigments as an island component and a water-soluble thermoplastic resin as a sea component; a step of impregnating an aqueous liquid that forms a colorless aqueous polymer elastomer into the voids of the fiber assembly of the sea-island type composite fibers, and then removing a portion of the aqueous liquid by extrusion; a step of drying and solidifying the aqueous polymer elastomer in the aqueous liquid imparted to the voids of the assembly of the sea-island type composite fibers; a step of dissolving and removing the water-soluble thermoplastic resin from the sea-island type composite fibers using an aqueous solvent to thereby obtain an artificial leather fabric of a fiber assembly of ultrafine fibers containing a non-water-soluble thermoplastic resin; and a step of polishing at least one side of the artificial leather fabric to make it napped, and the method does not include a step of dyeing the artificial leather fabric. According to such a manufacturing method, since it does not include a step of removing one component of the sea-island type composite fiber with an organic solvent and a step of wet-coagulating a polymer elastomer dissolved in a solvent with a liquid containing an organic solvent, the problem of elution of the color pigment contained in the island component does not occur.
[0017] Effects of the Invention
[0018] According to the present invention, a napped artificial leather having excellent color fastness to rubbing can be obtained, which can be colored in a wide range of tones from light to dark and has a non-white tone, and is unlikely to have a two-color feel on the napped surface even if the polymer elastic body is not colored. DETAILED DESCRIPTION
[0019] The napped artificial leather of the present embodiment comprises a fiber entanglement body formed by entanglement of ultrafine fibers, and a polymer elastic body impregnated into the fiber entanglement body, and has a napped surface formed by napping the ultrafine fibers on at least one side, wherein the ultrafine fibers contain 0.2 to 8% by mass of carbon black and 0.1 to 5% by mass of color pigments, and the total ratio of carbon black to color pigments is 0.3 to 10% by mass, the content ratio of the polymer elastic body is 0.1 to 15% by mass, the polymer elastic body is uncolored, and the ultrafine fibers are undyed. The napped artificial leather of the present embodiment is described in detail according to an example of its production method.
[0020] The napped artificial leather of the present embodiment is manufactured, for example, by the following manufacturing method, which at least includes: a step of preparing a fiber assembly of sea-island type composite fibers having a non-water-soluble thermoplastic resin containing 0.2 to 8% by mass of carbon black and 0.1 to 5% by mass of color pigments as an island component and a water-soluble thermoplastic resin as a sea component; a step of impregnating the voids of the fiber assembly of the sea-island type composite fibers with an aqueous liquid that forms a colorless aqueous polymer elastomer, and then removing a portion of the aqueous liquid by extrusion; a step of drying and solidifying the aqueous polymer elastomer in the aqueous liquid imparted to the voids of the fiber assembly of the sea-island type composite fibers; a step of dissolving and removing the water-soluble thermoplastic resin from the sea-island type composite fibers with an aqueous solvent to obtain an artificial leather fabric of a fiber assembly of ultrafine fibers containing a non-water-soluble thermoplastic resin; and a step of polishing at least one side of the artificial leather fabric to make it napped, and this method does not include the step of dyeing the artificial leather fabric. It should be noted that the ultrafine fibers in the present embodiment refer to fibers composed of island components obtained by removing the sea component from the sea-island type composite fibers.
[0021] First, the process of preparing a fiber entanglement body of sea-island type composite fibers having a water-insoluble thermoplastic resin containing 0.2 to 8 mass % of carbon black and 0.1 to 5 mass % of a color pigment as an island component and a water-soluble thermoplastic resin as a sea component is described.
[0022] As a method for manufacturing an entangled body of sea-island type composite fibers, there can be cited a method of melt-spinning the sea-island type composite fibers to manufacture a net and performing an entanglement treatment on the net. As a method for manufacturing a net of sea-island type composite fibers, there can be cited: a method of forming a net of long fibers by not cutting the sea-island type composite fibers of long fibers spun by a spunbond method or the like and capturing them on a net, a method of cutting the long fibers after melt spinning into short fibers to form a net of short fibers, etc. Among them, it is particularly preferred to use a net of long fibers from the perspective of easily adjusting the entangled state and obtaining a high sense of fullness. In addition, in order to give the formed net morphological stability, a melt bonding treatment can also be implemented. In addition, in any process before removing the sea component of the sea-island type composite fibers and forming ultrafine fibers, a fiber shrinkage treatment such as a heat shrinkage treatment using water vapor, hot water or dry heat can be implemented to densify the sea-island type composite fibers.
[0023] It should be noted that long fibers are not short fibers that are intentionally cut after spinning, but continuous fibers. Specifically, for example, they refer to filaments or continuous fibers that are not intentionally cut into short fibers with a fiber length of about 3 to 80 mm. The fiber length of the sea-island type composite fiber before ultrafine fiberization is preferably 100 mm or more, which is technically possible to manufacture, and can be several meters, hundreds of meters, several kilometers or longer as long as it is not inevitably cut during the manufacturing process.
[0024] The type of water-insoluble thermoplastic resin forming the island component in the sea-island type composite fiber is not particularly limited. Specifically, for example, there can be listed: aromatic polyesters such as polyethylene terephthalate (PET), isophthalic acid-modified PET, sulfonic acid isophthalic acid-modified PET, cationic dyeable PET, polybutylene terephthalate, and polyhexylene terephthalate; aliphatic polyesters such as polylactic acid, polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, and polyhydroxybutyrate-polyhydroxyvalerate resin; nylons such as nylon 6, nylon 66, nylon 10, nylon 11, nylon 12, and nylon 6-12; polyolefins such as polypropylene, polyethylene, polybutene, polymethylpentene, and chlorinated polyolefins, etc.
[0025] In the method for producing napped artificial leather of the present embodiment, in order to color the ultrafine fibers, 0.2 to 8% by mass of carbon black and 0.1 to 5% by mass of color pigments are blended into the resin of the island component.
[0026] Specific examples of carbon black include channel black, furnace black, thermal black, and Ketjen black.
[0027] In addition, color pigments are pigments that present colors other than black, gray, and white, i.e., non-colors, and are mainly organic pigments. Specific examples of such color pigments include: phthalocyanine pigments such as Pigment Blue 15:3, which is a copper phthalocyanine β crystal, anthraquinone pigments, quinacridone pigments, dichromatic pigments, Condensed polycyclic organic pigments such as oxazine pigments, isoindolinone pigments, isoindolinone pigments, indigo pigments, quinophthalone pigments, dione pyrrolopyrrole pigments, perylene pigments, pyrene pigments, benzimidazolone pigments, condensed azo pigments, azomethine azo pigments and other insoluble azo pigments; inorganic coloring pigments such as titanium oxide, red iron, chrome red, molybdenum red, methocarb, ultramarine, Prussian blue, iron oxide, etc. These color pigments present blue, red, green, yellow and other colors.
[0028] In addition to carbon black and color pigments, the ultrafine fibers may be formulated with other pigments, ultraviolet absorbers, heat stabilizers, deodorants, mildew preventers, various stabilizers, etc. as needed within the range that does not impair the effects of the present invention.
[0029] The method of adding carbon black and color pigment to the resin of the island component is not particularly limited. Specifically, for example, a method of kneading the water-insoluble thermoplastic resin, carbon black and color pigment used to form the island component of the ultrafine fibers in the above-mentioned content ratio using a mixing device such as an extruder can be cited.
[0030] The proportion of carbon black contained in the formed ultrafine fibers is 0.2 to 8% by mass, preferably 0.5 to 5% by mass, and more preferably 1 to 3% by mass from the perspective of easily obtaining a dark-colored napped artificial leather. When the content of carbon black in the ultrafine fibers is less than 0.2% by mass, the color rendering is poor, the color becomes whitish, and the color rendering is poor in high-quality. In addition, when the content of carbon black exceeds 8% by mass, the color rendering brought by the color pigment is difficult to become obvious, the effect of reducing the two-color sense becomes small, and the spinnability and physical properties are likely to be significantly reduced.
[0031] In addition, from the perspective of being able to color the napped artificial leather in a wide range of colors from light to dark and easily reducing the sense of two-color, the proportion of the color pigment contained in the formed ultrafine fiber is preferably 0.1 to 5% by mass, 0.5 to 4% by mass, and more preferably 1 to 3% by mass. When the content of the color pigment contained in the ultrafine fiber is less than 0.1% by mass, it is difficult to obtain the color development brought by the color pigment, and therefore it is difficult to reduce the sense of two-color. In addition, when the content of the color pigment contained in the ultrafine fiber exceeds 5% by mass, the color pigment becomes too much, so the spinning stability is likely to decrease.
[0032] In addition, the total ratio of carbon black and color pigment contained in the formed ultrafine fiber is 0.3 to 10% by mass, preferably 0.5 to 9% by mass. When the total ratio of carbon black and color pigment exceeds 10% by mass, the melt spinning property is reduced and the productivity is reduced. In addition, when the total ratio of carbon black and color pigment is less than 0.3% by mass, the colorability is reduced.
[0033] In addition, as the ratio of carbon black to color pigment contained in the formed ultrafine fibers, the color pigment / carbon black mass ratio is preferably 0.1 to 2.0, and more preferably 0.25 to 1.0. When the color pigment / carbon black mass ratio is less than 0.1, it is difficult to obtain color development due to the color pigment, and therefore it is difficult to reduce the two-color sense. In addition, when the color pigment / carbon black mass ratio exceeds 2.0, there is a tendency for poor color development.
[0034] In addition, as the water-soluble thermoplastic resin that becomes the sea component of the island-in-sea composite fiber, a water-soluble thermoplastic resin that has higher solubility in a solvent or higher decomposability by a decomposing agent than the resin of the island component can be selected. In addition, from the perspective of excellent spinning stability of the island-in-sea composite fiber, a water-soluble thermoplastic resin that has a low affinity with the water-insoluble thermoplastic resin that becomes the island component and has a lower melt viscosity and / or surface tension than the water-insoluble thermoplastic resin under spinning conditions is preferred. As a specific example of such a water-soluble thermoplastic resin, from the perspective of being able to be dissolved and removed by an aqueous medium without using an organic solvent, for example, a water-soluble polyvinyl alcohol resin (water-soluble PVA) is preferred.
[0035] The fineness of the island-in-sea composite fiber is not particularly limited. In addition, the average area ratio of the sea component to the island component in the cross section of the island-in-sea composite fiber (sea component / island component) is preferably 5 / 95 to 70 / 30, and more preferably 10 / 90 to 50 / 50. In addition, the number of microdomains of the island component in the cross section of the island-in-sea composite fiber is not particularly limited, but from the perspective of industrial productivity, it is preferably 5 to 1000, and more preferably about 10 to 300.
[0036] The following methods can be cited for the entanglement treatment: a method of stacking the web in multiple layers in the thickness direction using a stacking device, and then performing a needle punching treatment under the condition of simultaneously or alternately penetrating at least one hook (harb) from both sides thereof, or a method of performing a high-pressure water flow entanglement treatment. It should be noted that an oil agent or an antistatic agent can be applied to the web at any stage from the spinning step of the sea-island type composite fiber to the entanglement treatment.
[0037] Furthermore, if necessary, the web after the entanglement treatment can be subjected to a fiber shrinkage treatment such as a heat shrinkage treatment using water vapor, hot water or dry heat, or a heat press treatment to adjust the entanglement state and smoothing state of the web, thereby obtaining a nonwoven fabric as an entangled body of sea-island type composite fibers.
[0038] Next, the following process is described, which is a process of impregnating the voids of the entangled body of the sea-island type composite fiber with an aqueous liquid that forms an aqueous macromolecular elastic body, and then performing liquid squeezing to remove a part of the aqueous liquid, thereby adjusting the content of the macromolecular elastic body to 0.1 to 15% by mass. The macromolecular elastic body is a component that imparts morphological stability to the raised nap artificial leather.
[0039] In this step, an aqueous liquid forming an aqueous high molecular weight elastic body is impregnated into the gaps of the entangled body of the sea-island type composite fibers, and then the aqueous liquid is squeezed out appropriately, for example, by roller nipping treatment. Here, the aqueous high molecular weight elastic body refers to an aqueous liquid such as an emulsion, a dispersion, or a suspension prepared by dispersing it in an aqueous medium mainly composed of water by self-emulsification, forced emulsification, or suspension.
[0040] Specific examples of the polymer elastomer prepared as an aqueous liquid include polyurethane, acrylonitrile elastomer, olefin elastomer, polyester elastomer, polyamide elastomer, acrylic elastomer, etc. Among them, polyurethane is preferred. In addition, since the polymer elastomer is not colored, it does not substantially contain a pigment, but it can contain a pigment in a range that does not affect the process due to pigment contamination, that is, in a range where the polymer elastomer is substantially not colored, specifically in a range of 0 to 0.01 mass%.
[0041] That is, the content of the pigment in the polymer elastomer is preferably 0 to 0.01 mass %, more preferably 0 to 0.005 mass %, and particularly preferably 0 mass %. In this case, the polymer elastomer is not substantially colored, and thus it is preferred from the viewpoint of not affecting the process due to contamination. When the content of the pigment in the polymer elastomer exceeds 0.01 mass %, the polymer elastomer is colored, and there is a risk that the pigment will remain and affect the process due to contamination. In this case, there is a tendency for the productivity of small-quantity, multi-variety production to decrease.
[0042] The aqueous liquid of the polymer elastic body can be mixed with coagulation regulators such as gelling agents, antioxidants, ultraviolet absorbers, fluorescent agents, mildewproof agents, penetrants, defoamers, lubricants, water repellents, oil repellents, thickeners, extenders, curing accelerators, foaming agents, water-soluble polymer compounds such as polyvinyl alcohol and carboxymethyl cellulose, inorganic particles, conductive agents, etc. as needed. In particular, when the content ratio of the polymer elastic body is adjusted to 0.1 to 15% by mass, it is particularly preferred to include a thermosensitive gelling agent that gels the aqueous liquid of the polymer elastic body in order to make the polymer elastic body difficult to be exposed on the napped surface.
[0043] Specific examples of the thermosensitive gelling agent include, for example, zinc oxide, potassium sulfate, sodium sulfate, alkylphenol formalin condensate oxyalkylene adducts, polyether formal, polyvinyl methyl ether, polypropylene glycol, polyoxyalkylene modified polysiloxane, water-soluble polyamide, starch, methyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, protein, carbonate, bicarbonate, polyphosphate, etc. The content of the thermosensitive gelling agent varies depending on the type of the thermosensitive gelling agent, and is preferably 0.01 to 30 parts by mass relative to 100 parts by mass of the polymer elastomer (solid content).
[0044] In this process, the aqueous liquid of the polymer elastic body is impregnated into the gaps of the entangled body of the sea-island type composite fiber, and then, for example, by roller clamping treatment, the aqueous liquid is squeezed appropriately. In this way, the content of the polymer elastic body contained in the obtained napped artificial leather can be adjusted to 0.1-15% by mass. By adjusting the content of the polymer elastic body contained in the napped artificial leather to 0.1-15% by mass, the uncolored polymer elastic body is not easy to be exposed on the napped surface of the napped artificial leather, and the color unevenness can be made less obvious. In the case where the content of the polymer elastic body contained in the napped artificial leather exceeds 15% by mass, the uncolored polymer elastic body is easy to be exposed on the napped surface of the napped artificial leather, the color unevenness becomes conspicuous, and the two-color feeling is easy to feel.
[0045] Then, the polymer elastic body in the aqueous liquid provided to the gaps of the entangled body of the sea-island type composite fiber is coagulated. As a method for coagulating the polymer elastic body from the aqueous liquid, there is a method of drying the entangled body of the sea-island type composite fiber impregnated with the aqueous liquid at a temperature of about 120 to 170°C. In addition, when the aqueous liquid is an emulsion, the aqueous liquid is subjected to a wet heat treatment to gelate it, and then dried, thereby suppressing migration to the surface layer.
[0046] Then, the sea component is removed from the island-in-sea composite fiber to produce an artificial leather fabric of a fiber entanglement body containing ultrafine fibers. As a method for removing the sea component from the island-in-sea composite fiber, there can be cited a method of dissolving or decomposing the sea component in the island-in-sea composite fiber with a solvent or decomposition agent that can selectively remove only the sea component.
[0047] The average fineness of the ultrafine fibers is preferably 1.5 dtex or less, more preferably 0.005 to 1 dtex, and particularly preferably 0.1 to 0.5 dtex. When the average fineness of the ultrafine fibers is too high, the density of the napped surface is reduced, and a high-grade appearance cannot be obtained, or the soft feel tends to be reduced. It should be noted that the fineness is obtained by the following method: a cross section parallel to the thickness direction of the napped artificial leather is photographed at 3000 times magnification using a scanning electron microscope (SEM), and the diameter of 15 fibers selected from the whole is calculated using the density of the resin forming the fibers, and the average value is obtained.
[0048] The artificial leather fabric thus obtained comprises a fiber entanglement of ultrafine fibers and a polymer elastic body impregnated into the entanglement of ultrafine fibers. The artificial leather fabric can be sliced in the thickness direction to adjust the thickness as needed to obtain an artificial leather fabric of a given thickness.
[0049] In addition, by grinding at least one side of the artificial leather fabric, a napped artificial leather with ultrafine fibers on the surface can be obtained. The grinding method can be a method of grinding using sandpaper or emery paper preferably with a number of 120 to 600, more preferably about 240 to 600. In this way, a napped artificial leather having a napped surface with ultrafine fibers that have been raised on one side or both sides can be obtained.
[0050] For the raised-napped artificial leather, in order to further adjust the feel, it is also possible to implement shrinkage processing to impart softness, kneading softening treatment, or reverse sealing brushing, anti-fouling treatment, hydrophilic treatment, lubricant treatment, softener treatment, antioxidant treatment, ultraviolet absorber treatment, fluorescent agent treatment, flame retardant treatment and other finishing treatments.
[0051] In addition, in order to suppress the shedding of napped fibers and improve the appearance quality and surface properties of the napped surface, a polymer elastic body may be further applied to the surface layer of the napped surface of the artificial leather fabric in a manner that does not bind the napped roots, as required. As a method for applying a polymer elastic body in a manner that does not bind the napped roots, for example, a method of gravure coating a polymer elastic body aqueous dispersion or a solvent-based polymer elastic body solution from the napped surface side can be cited.
[0052] When the polymer elastic body is applied to the napped surface of the artificial leather fabric, the amount applied is preferably 0.2 to 4 g / m2 in terms of solid content from the viewpoint of excellent balance between the high-quality appearance of the napped surface and the anti-pilling property. 2 , and more preferably 0.5 to 3 g / m 2 The proportion of the polymer elastic body to be applied to the napped surface is preferably 0.1 to 1.0% by mass, more preferably 0.15 to 0.8% by mass, based on the solid content, from the viewpoint of an excellent balance between the high-grade appearance of the napped surface and the anti-pilling property.
[0053] The napped artificial leather of the present embodiment thus manufactured can be colored to a target color in a wide range of colors from light to dark by mixing carbon black and color pigments in the ultrafine fibers. In addition, since the polymer elastomer is not easily exposed on the napped surface, the napped artificial leather of the present embodiment is not easily noticeable in color unevenness, the color fastness of the coloring is also high, and the productivity is also excellent.
[0054] The color of the napped surface of the napped artificial leather of this embodiment is not particularly limited. From the perspective that the polymer elastic body is not easily exposed on the napped surface and the effect of making color unevenness less noticeable becomes significant, the color coordinate space (L * a * b * The brightness L in the color space) * The value is preferably 25 or less, and more preferably 17 or less. In addition, from the perspective of maintaining high color fastness even in a dark color, a * The value is in the range of -2.5 to 2.5, b * The value ranges from -2.5 to 2.5.
[0055] It should be noted that the existing napped artificial leather is often colored by dyeing, but the napped artificial leather of the present embodiment is an undyed non-dyed napped artificial leather. Since the napped artificial leather is not dyed, the dyeing process can be omitted. In addition, since the polymer elastomer is not colored, when a small amount of multi-variety production is required, the operation of switching the concentration of the pigment in the aqueous liquid of the polymer elastomer according to the variety can be omitted. In addition, since the polymer elastomer is not colored and the ultrafine fiber is not dyed, when rubbed with other fabrics, a napped artificial leather with excellent rubbing resistance color fastness can be obtained, and the dye is not easily transferred to other fabrics.
[0056] The thickness of the napped artificial leather produced as described above is not particularly limited, but is preferably 0.3 to 1.5 mm, and more preferably 0.4 to 1.0 mm. The weight per unit area of the napped artificial leather is also not particularly limited, but is preferably 150 to 600 g / m 2, more preferably 200 to 500 g / m 2 .
[0057] The apparent density of the napped artificial leather is not particularly limited, but is preferably 0.4 to 0.7 g / cm2 from the viewpoint of obtaining a napped artificial leather having an excellent balance between a full feel and a soft feel. 3 , more preferably 0.45 to 0.6 g / cm 3 .
[0058] Example
[0059] The present invention will be described in more detail below by way of examples. It should be noted that the scope of the present invention is not limited by the examples.
[0060] [Example 1]
[0061] Thermoplastic water-soluble polyvinyl alcohol (PVA) as a sea component and isophthalic acid-modified polyethylene terephthalate (IP-modified PET) as an island component were prepared. The isophthalic acid-modified polyethylene terephthalate was added with 1.5% by mass of carbon black and 1.0% by mass of color pigments in total. The color pigments included phthalocyanine blue organic pigments (copper phthalocyanine β-crystal Pigment Blue 15:3) and diphthalocyanine blue organic pigments. The oxazine-based purple organic pigment was ejected using a melt-compounding nozzle having 12 islands per one sea-island type composite fiber, with the pressure adjusted so that the mass ratio of the sea component / island component was 25 / 75, and the nozzle temperature was set at 260° C. Then, the ejected molten strand was stretched to spin a sea-island type composite fiber with a fineness of 3.3 dtex.
[0062] Then, the sea-island composite fibers were continuously deposited on a movable net and lightly pressed with a heated metal roller to suppress burrs on the surface. Then, the sea-island composite fibers were peeled off from the net and passed between the heated metal roller and the backing roller under pressure. Thus, a 32 g / m2 sheet with a unit area weight of 1.5 g / m2 was produced. 2 The network.
[0063] The obtained web was folded using a folding device to a total weight per unit area of 380 g / m 2 The overlapping net was made by stacking 12 layers in a way, and the anti-broken needle oil was evenly applied by spraying. Then, the needles were alternately sprayed from both sides at 3300 thorns / cm 2 The overlapping web was needle punched to obtain an entangled web. The unit area weight of the entangled web was 500 g / m 2 Then, the entangled web was treated at 70°C and 50% RH for 30 seconds to shrink by moisture and heat. Thus, a fiber entanglement body of sea-island type composite fibers was produced.
[0064] Then, the fiber entanglement body of the sea-island type composite fiber was impregnated with a polyurethane emulsion containing no pigment. The polyurethane emulsion contained 15% by mass of a self-emulsifying amorphous polycarbonate polyurethane having a 100% modulus of 3.0 MPa as a solid component and 2.5% by mass of ammonium sulfate as a thermosensitive gelling agent. Then, the fiber entanglement body of the sea-island type composite fiber impregnated with the polyurethane emulsion was passed through the gap between the nip rolls to squeeze the emulsion.
[0065] Then, the emulsion imparted to the fiber entanglement of the sea-island type composite fiber was subjected to a wet heat treatment to gel, and then dried at 150°C to solidify the aqueous polyurethane. Then, the fiber entanglement of the sea-island type composite fiber after the aqueous polyurethane was solidified was repeatedly padded in hot water at 95°C to dissolve and remove the PVA, and then dried. Thus, a fiber entanglement of ultrafine fibers in which 12 fiber bundles of ultrafine fibers with a fineness of 0.2 dtex were three-dimensionally entangled was generated. Thus, an artificial leather fabric in which 10% by mass of aqueous polyurethane was imparted to the gaps of the fiber entanglement of the ultrafine fibers was obtained.
[0066] Then, the artificial leather fabric is divided into two parts along the thickness direction, and the reverse slice surface is further polished to form a nap surface. Then, the water dispersion of polycarbonate polyurethane is gravure coated on the artificial leather fabric with the nap surface in a manner that gives a solid content ratio of 0.7% by mass, and then dried at 135°C. Then, a softening treatment is performed using a liquid flow dyeing machine that does not contain a dye, and further drying and brushing are performed to obtain a suede-like nap artificial leather. The obtained nap artificial leather is black with a bluish color, and the weight per unit area is 230g / m 2 , the apparent density is 0.48g / cm 3 .
[0067] Then, the obtained napped artificial leather was evaluated according to the following evaluation method.
[0068] 〈Chroma〉
[0069] The L of the surface of the cut napped artificial leather was measured using a spectrophotometer (CM-3700 manufactured by Minolta) in accordance with JIS Z 8729. * a * b * Chromaticity of the colorimetric system. Calculate the average value of the chromaticity of three points measured at the average position selected from the entire test piece. * The smaller the value, the darker the color.
[0070] 〈Uneven color〉
[0071] A sample of 50 cm square of napped artificial leather was prepared and cut into pieces, and five expert evaluators evaluated the presence or absence of two-tone feeling. Then, the case where more people evaluated that there was no two-tone feeling was marked as A, and the case where more people evaluated that there was two-tone feeling was marked as B.
[0072] 〈Melt spinnability〉
[0073] A: In melt spinning, there is little fiber breakage and continuous productivity is possible.
[0074] B: During melt spinning, fiber breakage and the like frequently occur, and continuous productivity is not possible.
[0075] 〈Color fastness to rubbing〉
[0076] A multi-fiber interwoven fabric (interwoven No. 1) was prepared by weaving cotton, nylon, acetate, wool, rayon, acrylic, silk, and polyester fabrics in parallel as specified in Annex JA of JIS L 0803. Then, the color fastness to rubbing in dry and wet conditions was measured in accordance with JIS L 0849 (Test method for color fastness to rubbing).
[0077] Specifically, the color fastness to rubbing was measured as follows using ATLAS Crockmeter CM-5 (manufactured by ATLAS ELECTRIC DEVICES CO).
[0078] In the case of the color fastness to rubbing when dry, the dried multi-fiber interwoven fabric was mounted on a glass friction member. Then, the multi-fiber interwoven fabric mounted on the friction member was brought into contact with the napped surface of a part of the napped artificial leather with a load of 900 g, and reciprocated 10 times. Then, the multi-fiber interwoven fabric was removed, and Cellotape (registered trademark) was attached to the contaminated part of the multi-fiber interwoven fabric, and reciprocated once with a cylindrical load of 1.5 pounds, and then the Cellotape was peeled off from the multi-fiber interwoven fabric.
[0079] On the other hand, in the case of the color fastness to friction when wet, a wet multi-fiber interwoven fabric which was immersed in distilled water and then the excess water was removed was attached to a glass friction member. Then, the multi-fiber interwoven fabric attached to the friction member was brought into contact with the napped surface of a part of the napped artificial leather with a load of 900 g, and was reciprocated 10 times. Then, the multi-fiber interwoven fabric was removed and dried in an environment below 60°C. Then, Cellotape was attached to the contaminated part of the multi-fiber interwoven fabric, and was reciprocated once with a cylindrical load of 1.5 pounds, and then the Cellotape was peeled off from the multi-fiber interwoven fabric.
[0080] Then, the change of color transfer to cotton white cloth in dry and wet state was judged according to the gray scale for pollution (5 levels to 1 level). The gray scale for pollution was used to judge the level of various woven fabrics, and the level of the woven fabric with the most polluted raw material was used as the level of color transfer resistance.
[0081] 〈Appearance〉
[0082] A test piece of 20 cm×20 cm was cut out from the napped artificial leather, and the appearance of the test piece was visually observed according to the following criteria.
[0083] A: Neither granular white spots nor black spots of the polymer elastic body were observed by naked eye.
[0084] B: Granular white spots or black spots of the polymer elastic body were observed with the naked eye.
[0085] 〈Touch〉
[0086] A test piece of 20 cm×20 cm was cut out from the napped artificial leather, and the touch of the surface of the test piece was evaluated according to the following criteria.
[0087] A: Smooth touch.
[0088] B: The surface feels rough.
[0089] The results are shown in Table 1 below.
[0090]
[0091] [Example 2]
[0092] In Example 1, except that the island component resin was changed to an isophthalic acid-modified polyethylene terephthalate having a modification degree of 6 mol% to which 0.5 mass % of carbon black and 0.3 mass % of a color pigment were added, a napped artificial leather was obtained in the same manner as in Example 1. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0093] [Example 3]
[0094] In Example 1, except that the island component resin was changed to an isophthalic acid-modified polyethylene terephthalate having a modification degree of 6 mol% to which 5 mass % of carbon black and 3.3 mass % of a color pigment were added, a napped artificial leather was obtained in the same manner as in Example 1. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0095] [Example 4]
[0096] In Example 1, except that 1.0 mass % of the color pigment was changed to 0.3 mass %, a napped artificial leather was obtained in the same manner as in Example 1. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0097] [Example 5]
[0098] In Example 1, except that the color pigment content was changed from 1.0 mass % to 3.0 mass %, a napped artificial leather was obtained in the same manner as in Example 1. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0099] [Example 6]
[0100] A napped artificial leather was obtained in the same manner as in Example 1 except that a fiber entangled body including a fiber bundle containing 12 ultrafine fibers having a fineness of 0.1 dtex was used as the fiber entangled body. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0101] [Example 7]
[0102] A napped artificial leather was obtained in the same manner as in Example 1 except that a fiber entangled body including a fiber bundle containing 12 ultrafine fibers having a fineness of 0.3 dtex was used as the fiber entangled body. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0103] [Example 8]
[0104] In Example 1, a napped artificial leather was obtained in the same manner as in Example 1 except that a fiber-entangled body containing isophthalic acid-modified polyethylene terephthalate having a modification degree of 6 mol% to which 0.5 mass % of carbon black and 0.3 mass % of color pigment were added and containing a fiber bundle containing 12 ultrafine fibers having a fineness of 0.3 dtex was used as the fiber-entangled body. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0105] [Example 9]
[0106] A napped artificial leather was obtained in the same manner as in Example 1 except that the fineness of the ultrafine fiber was changed to 1.5 dtex. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0107] [Example 10]
[0108] In Example 1, a napped artificial leather was obtained in the same manner as in Example 1, except that 1% by mass of aqueous polyurethane was added to the voids of the fiber entanglement body of the ultrafine fibers instead of 10% by mass of aqueous polyurethane. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0109] [Example 11]
[0110] In Example 1, a napped artificial leather was obtained in the same manner as in Example 1, except that 15% by mass of aqueous polyurethane was added to the voids of the fiber entanglement body of the ultrafine fibers instead of 10% by mass of aqueous polyurethane. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0111] [Comparative Example 1]
[0112] In Example 1, a napped artificial leather was obtained in the same manner as in Example 1, except that a color pigment was not added to the ultrafine fibers. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0113] [Comparative Example 2]
[0114] In Example 3, a napped artificial leather was obtained in the same manner except that 6.0% by mass of color pigment was added to the ultrafine fibers instead of 3.3% by mass of color pigment. The obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0115] [Comparative Example 3]
[0116] In Example 1, except that the aqueous polyurethane was not provided to the voids of the fiber entanglement body of the ultrafine fibers, a napped artificial leather was obtained in the same manner as in Example 1. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0117] [Comparative Example 4]
[0118] In Example 1, a napped artificial leather was obtained in the same manner as in Example 1, except that 20% by mass of aqueous polyurethane was added to the voids of the fiber entanglement body of the ultrafine fibers instead of 10% by mass of aqueous polyurethane. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0119] [Comparative Example 5]
[0120] In Example 1, except that 5% by mass of carbon black was added to the aqueous polyurethane to be impregnated in the gaps of the fiber entanglement body of the ultrafine fibers to color it, a napped artificial leather was obtained in the same manner as in Example 1. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0121] [Comparative Example 6]
[0122] In Example 1, except that the isophthalic acid-modified polyethylene terephthalate to which 4.5% by mass of a phthalocyanine blue organic pigment (copper phthalocyanine β-crystal Pigment Blue 15:3) was added as the color pigment, a napped artificial leather was obtained in the same manner as in Example 1. Then, the obtained napped artificial leather was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0123] Referring to Table 1, the color fastness to rubbing of the napped artificial leathers obtained in Examples 1 to 11 of the present invention is 4-5 when dry and 3-4 when wet, and can achieve L * The coloring of a wide range of colors such as values of 14 to 32 is performed, and no color unevenness is observed on the napped surface, and the appearance does not show a two-color feeling. On the other hand, the appearance of the napped artificial leather obtained in Comparative Example 1 that does not contain color pigments has a two-color feeling. In addition, the melt spinnability of the napped artificial leather obtained in Comparative Example 2 in which the total ratio of carbon black to color pigments is 11% by mass is poor. In addition, the napped artificial leather obtained in Comparative Example 3 that is not impregnated with water-based polyurethane has a rough touch. In addition, the appearance of the napped artificial leather obtained in Comparative Example 4 that is impregnated with 20% by mass of water-based polyurethane shows a two-color feeling. In addition, the napped artificial leather obtained in Comparative Example 5 that is impregnated with water-based polyurethane added with 5% by mass of carbon black is observed to have a two-color feeling caused by black spots of polyurethane. Comparative Example 6 using isophthalic acid-modified polyethylene terephthalate without using carbon black and adding only 4.5 mass % of color pigment had poor spinnability, a whitish color tone, a poor sense of luxury, and poor color fastness to rubbing.
Claims
1. A napped artificial leather comprising: a fiber entangled body formed by entangled ultrafine fibers having an average fineness of 0.1 to 0.3 dtex, and a polymer elastic body impregnated into the fiber entangled body, wherein the napped artificial leather has a napped surface formed by raising the ultrafine fibers on at least one side, wherein: The ultrafine fibers contain 0.2 to 3% by mass of carbon black and 0.1 to 5% by mass of color pigments. The color pigment at least comprises phthalocyanine pigment and diphthalocyanine pigment. Oxazine pigments, The mass ratio of the color pigment to the carbon black is 0.1 to 2.0, The content ratio of the polymer elastic body in the napped artificial leather is 0.1 to 15% by mass. The polymer elastic body is not colored, and the ultrafine fibers are not dyed. The hair standing surface is in the color coordinate space L * a * b * Brightness L in color space * The value ranges from 20 to 32. * The value is in the range of -2.5 to 2.5, b * The value ranges from -2.5 to 2.
5.
2. A method for manufacturing a napped artificial leather, which is the method for manufacturing a napped artificial leather according to claim 1, the method comprising at least: A process for preparing a fiber entanglement body of sea-island type composite fibers having a water-insoluble thermoplastic resin containing 0.2 to 3% by mass of the carbon black and 0.1 to 5% by mass of the color pigment as an island component and a water-soluble thermoplastic resin as a sea component; The step of impregnating the voids of the fiber entanglement body of the sea-island type composite fiber with an aqueous liquid for forming a non-colored aqueous high molecular weight elastic body, and then removing a portion of the aqueous liquid by squeezing; A step of drying and solidifying the aqueous high molecular weight elastic body in the aqueous liquid provided to the gaps in the fiber entanglement body of the sea-island type composite fibers; A step of dissolving and removing the water-soluble thermoplastic resin from the sea-island type composite fibers using an aqueous solvent to obtain an artificial leather fabric comprising a fiber entanglement body of ultrafine fibers of the water-insoluble thermoplastic resin; and The step of polishing at least one side of the artificial leather fabric to make it stand up. Furthermore, the method does not include a step of dyeing the artificial leather grey cloth.
Citation Information
Patent Citations
Sueded artificial leather and method for producing the same
JP2004143654A
Measuring device for state of adhesion of scale in boiler system
JP1984021903A
Napped artificial leather
WO2019159728A1